PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK KELAS V SD SE-GUGUS IV SEDAYU BANTUL - Rohmah, Siva Nur; Siti Maisaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The focus of this study is to ascertain a) the school environment in Cluster IV Sedayu elementary schools, b) character formation in Cluster IV Sedayu elementary schools, and c) the impact of the school environment on the character development of grade V students in Cluster IV Sedayu elementary schools. Quantitative survey research is the methodology employed. 84 individuals, all in grade 5, who attended elementary schools in Cluster IV Sedayu Bantul, made up the study's population. Since there were less than 100 individuals in the population, the saturation sampling technique was employed. Questionnaires and observation were the methods employed in this study to collect data. Simple regression analysis was the data analysis method employed. Based on data analysis, the study's findings showed that the average value (ideal mean) in the classroom was 90.11 with a standard deviation of 9,568. This placed it in the good category with a percentage of 51.4% in the class 82.5≤X<97.5, while the average value (ideal mean) in the development of student character was 86.65 with a standard deviation of 10,764, placing it in the good category with a percentage of 51.4% in the interval class 82.5≤X<97.5. The information was derived from the F Test, which yielded a computed F value of 71,457 and a significance level of 0.037 <0.05.The conclusion is that the school environment has a significant effect on the formation of student character. Therefore, schools must always implement a good teaching and learning process, implement school culture, extracurricular activities and communication with parents of students.